The Value of traditional Seloko Jambi as a KIPAS Counseling Technique in Developing Social Skills of senior Hight School Students - Suci Nora Julina Putri (Proceedings Series of Educational Studies, 2023)
Counselors play an important role in the process of developing students' social skills, so appropriate solutions are needed so that students' problems are immediately resolved. The Jambi Malay traditional seloko is used as an alternative solution because it contains expressions and messages of benevolence that are able to have a positive impact on the lives of each individual.  Traditional of seloko Jambi as a KIPAS counseling technique with a group format. KIPAS Counseling is a counseling based on Indonesian culture which provides joy in the implementation process. This research is descriptive qualitative research with a literature study concept that describes the results of previous research that have been collected. Data collection techniques use observation and literature study. The data analysis technique in this research uses content analysis with a qualitative paradigm. The research results found that the values of traditional Seloko Jambi have an important role in developing the social skills of senior Hight School Students, because they teach positive interaction concepts such as courtesy, religion, self-adjustment, cooperation and mutual respect.